Application of the Barcelona Clinic Liver Cancer therapeutic strategy and impact on survival. Issue 3 (1st June 2015) - Hernández-Guerra, Manuel; Hernández-Camba, Alejandro; Turnes, Juan; Ramos, Luis Martin; Arranz, Laura; Mera, José; Crespo, Javier; Quintero, Enrique
Abstract : Background: The Barcelona Clinic Liver Cancer (BCLC) classification of hepatocellular carcinoma (HCC) has proved useful in the management of HCC patients. However, BCLC‐recommended first‐line treatment is not always applicable in clinical practice. Objective: We performed a multicentre retrospective analysis of reasons for deviation from first‐line treatment in 2008–2012. Methods: One to three‐year survival data were analysed using Kaplan‐Meier method. Results: A total of 407 consecutive HCC patients (66.6 ± 3 years, 83% male) with cirrhosis were included. Tumours were detected during surveillance in 53% of patients, grouped as Child‐Pugh A (67%), B (25%) and C (8%); and BCLC A (including stage 0, 44%), B (26%), C (15%) and D (15%). In 31% of patients, first‐line treatment was not feasible (51% in early stages) due to: technical reasons (74%); patient non‐conformity (20%); medical decision (3%); and disease progression (3%). One to three‐year survival of patients not receiving the recommended first‐line treatment was similar to that of patients treated according to BCLC recommendations (log‐rank, p =  0.229). Conclusion: In real‐life practice one‐third of HCC patients could not receive first‐line BCLC treatment. In our cohort of patients, similar short and medium‐term survival was observed. Long‐term prospective studies are required to determine the best alternative treatment option when BCLC first‐line treatment is not feasible.